Fertilisation with ash from biomass combustion and gypsum on physical properties of sandy soil - Dariusz Błażejczak; Marek Śnieg; Magdalena Sobolewska; Anna Jaroszewska; Jarosław Pytka; Krzysztof Kuglarz (Journal of Water and Land Development)
The aim of the present paper was to verify the hypothesis that a single application of specific dose of ash from biomass combustion and/or gypsum has a positive effect on physical properties of sandy soil and that the said effect disappears over the following years. The following were determined in the layer of 5–10 cm: penetration resistance (PR), vane shear resistance (Ss), gravimetric moisture content (ww), dry bulk density (BD), moisture content (WpF2) and air-filed porosity (PApF2) at water potential pF2. At pF2, susceptibility to soil compaction was analysed i.e., unit stress required to cause soil deformation of an assumed value of 1.0 mm (P1) or 2.0 mm (P2). Fertilisation with ash and/or gypsum at doses of 15 and 3 Mg∙ha−1 respectively, affects the physical properties of soil particularly in the first year following the application and that the said fertilisation is to be conducted every two years. It was found that fertilisation with ash has a particularly positive effect on ww. The loosening effect of fertilisation with ash, measured with BD, was poorly pronounced. A decrease in PR and Ss values was observed particularly in the first year. The analyses at water potential pF2 showed that fertilisation with ash or ash with the addition of gypsum has a positive effect on the properties under analysis. The effect of fertilisation with gypsum at a dose of 3 Mg∙ha−1 on the analysed properties was inconclusive.